MEDIA DALAM PEMBERITAAN TANJUNG BALAI ASAHAN (STUDI ANALISIS FRAMING TENTANG KERUSUHAN TANJUNG BALAI ASAHAN DI REPUBLIKA.CO.ID): Alna Hanana, Arif Mulizar - Jurnal COMMED (Commed : Jurnal Komunikasi dan Media, 2017)
Media has the ability to construct reality. One of them is by framing the news done by the media. This research was conducted to find out how Republika.co.id frame the report of SARA issues in Tanjung Balai Asahan Riot, North Sumatera. This research uses qualitative method with framing model analysis by Robert N. Entman. The results of this study indicate that Republika.co.id sided with Islam and did not provide news containing opinions from other perspectives. This can be seen from the analysis in four categories, which are the definition of the problem, the approximate source of the problem, the moral judgment of the problem, and the settlement of the problem. The news state that the riots have begun conducive and the cause is a nonMuslim citizen. They also present moral values such as restraint and tolerance, legal and communication solutions.